OP0269-HPR Annual Review for Inflammatory Arthritis Patients - A NICE Extra but A Challenge to Implement. (10th June 2014) - Cornell, P.; Wright, S.; Christopher, J.; Thompson, P.
Abstract : Background: Rheumatoid Arthritis (RA) is associated with an increased risk of cardiovascular disease along with co-morbidities that include osteoporosis and depression. Complications can also arise that include vasculitis, disease of the cervical spine, lung or eyes. The National Institute of Clinical Excellence (NICE CG79) issued guidance for the care of patients with RA which concluded that patients should be assessed annually for these complications along with disease activity assessment, the need for surgical intervention and the impact of the disease on patients lives. We currently treat over a 1000 patients with RA and developed annual review clinics in 2010 to meet NICE CG79 and the aim was to audit our compliance with NICE CG79, whether annual review clinics resulted in extra clinic appointments due to flare of disease, increased contacts via telephone advice line during the year preceding annual review and to implement change if areas of improvement identified. Methods: The criteria for patients to be enrolled in the annual review clinic were; stable or no escalation of DMARDs in the previous year, compliant with DMARD blood monitoring regime, no evidence of active systemic involvement, stable inflammatory markers for at least 6 months, no more than one urgent appointment or IM cortisone injection in the last year and patient and/or carer/partner able to recognise a flare of arthritis and seek appropriate help. Patients were then assessed annually against a variety of criteria which included cardiovascular risk, osteoporosis risk, complications from RA and the impact of RA on their lives. Results: All patients who attended the annual review clinic from April 2012 - March 2013 were assessed against the criteria. 84 patients were included in the audit, this included 60 RA patients M:F 28:32 RhFactor +ve 40, 24 PsA patients M:F 17:7, average age 69.8, spread 43 - 89 years. Disease activity DAS28 was assessed on the RA patients only (n=60), Remission (DAS28 <2.6) 38, Low disease activity (DAS28 2.61 - 3.1) 12, Moderate disease activity (DAS28 3.11 - 5.1) 9, Severe disease activity (DAS 28 >5.1) 0). Only 3 unscheduled appointments took place during the year. Ten patients used the telephone advice line but only 2 patients used it twice during the year. Conclusions: Annual review was appropriate as patients fulfilled NICE criteria. However, the Health, Anxiety and Depression (HADs) questionnaire was time consuming, although we didn't measure the exact time it took for each patient to complete but therefore to reduce the time it was decided to change the HADs to the PHQ9. According to NICE all patients with RA should be offered annual review and the clinic slots are 15 minutes longer to take account of the extra assessments but we are now looking at how we can implement this across all rheumatology clinics using specifically designed proformas to capture the information. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1291